2017
DOI: 10.3892/ol.2017.6220
|View full text |Cite
|
Sign up to set email alerts
|

Predictive role of human equilibrative nucleoside transporter 1 in patients with pancreatic cancer treated by curative resection and gemcitabine-only adjuvant chemotherapy

Abstract: The predictive roles of human equilibrative nucleoside transporter 1 (hENT-1) in patients who undergo curative resection and adjuvant chemotherapy with gemcitabine alone have not been established. The present study retrospectively analyzed the clinical data from 101 consecutive patients who underwent curative resection and who received gemcitabine adjuvant chemotherapy for the treatment of pancreatic cancer at Kanagawa Cancer Center (Yokohama, Japan) between 2005 and 2014. The associations between the hENT-1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In a subanalysis of the ESPAC-3 trial population, which was a comparative study between gemcitabine and 5-fluorouracil based chemotherapy in PDAC patients, hENT1 expression was identified as a predictive biomarker of the response to gemcitabine without any hENT-1-dependent difference observed in the fluorouracil group [ 104 ]. Aoyama and colleagues reported that patients with high hENT1 expression in PDAC tissue and treated with curative resection and adjuvant gemcitabine had a higher overall survival at five years (high hENT1: 20.6% vs. low hENT1: 8.9%; p = 0.019) and disease-free survival rates at three years (high hENT1: 23.8% vs. low hENT1: 9.4%; p = 0.024) post-procedure [ 105 ]. In their meta-analysis, Bird et al showed benefits in both disease-free (hazard ratio: 0.58; 95% CI: 0.42–0.79) and overall survival (hazard ratio: 0.52; 95% CI: 0.38–0.72) in PDAC patients with high hENT1 expression and adjuvant gemcitabine chemotherapy after PDAC resection [ 106 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…In a subanalysis of the ESPAC-3 trial population, which was a comparative study between gemcitabine and 5-fluorouracil based chemotherapy in PDAC patients, hENT1 expression was identified as a predictive biomarker of the response to gemcitabine without any hENT-1-dependent difference observed in the fluorouracil group [ 104 ]. Aoyama and colleagues reported that patients with high hENT1 expression in PDAC tissue and treated with curative resection and adjuvant gemcitabine had a higher overall survival at five years (high hENT1: 20.6% vs. low hENT1: 8.9%; p = 0.019) and disease-free survival rates at three years (high hENT1: 23.8% vs. low hENT1: 9.4%; p = 0.024) post-procedure [ 105 ]. In their meta-analysis, Bird et al showed benefits in both disease-free (hazard ratio: 0.58; 95% CI: 0.42–0.79) and overall survival (hazard ratio: 0.52; 95% CI: 0.38–0.72) in PDAC patients with high hENT1 expression and adjuvant gemcitabine chemotherapy after PDAC resection [ 106 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…In addition, cells were incubated with anti-ENT-1 primary antibody (Abcam) and anti-rabbit-alexa fluor 647 conjugated secondary antibody (Cell Signaling) (hENT-1 antibody assessment provided in Supplementary). The staining intensity for hENT-1 in individual CTC and the percentage of hENT-1 positive CTCs were scored based on the immunohistochemical scoring system (28,29). The staining intensity of hENT-1 was divided into four levels: 0, no staining; 1, weakly positive; 2, moderately positive and 3, strongly positive (Figure 1C); the positive percentage was assigned a score ranging from 0 to 3: 0, ≤5% positive cells; 1, 5-25% positive cells; 2, 25-50% positive cells; 3, >50% positive cells.…”
Section: Immunofluorescence Analysismentioning
confidence: 99%
“…Immunohistochemistry (IHC) analyses were performed as previously described (28,29). Formalin-fixed, paraffinembedded (FFPE) tumor tissues from PDAC patients were deparaffinized with xylene, rehydrated with ethanol and boiled for 20 minutes in microwave for antigen retrieval in a 10-mM citrate buffer (pH 6).…”
Section: Immunohistochemistry Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Human equilibrative nucleoside transporter 1 (hENT1) is the primary facilitative transporter of GEM [6]. High levels of hENT1 were correlated with high GEM concentration in cancer cells and increases drug e cacy [7,8]. Previous studies have indicated that high hENT1 expression was associated with longer overall survival (OS) among patients treated with both palliative and adjuvant GEM [9,10] and vice versa [11,12].…”
Section: Introductionmentioning
confidence: 99%